Pengaruh Net Profit Margin, Long Term Debt To Equity Ratio,Debt To Equity Ratio, Total Asset Turn Over Ratio Terhadap Return On Asset Pada PT. Nippon Indosari Corpindo Tbk - Amalia Nuroktofiana; Alwi Bima; Nurul Huda (Universitas 45 Surabaya, 2023)
The purpose of this research is to determine the effect of Net Profit Margin, Long Term Debt To Equity Ratio, Debt To Equity Ratio, Total Asset Turn Over Ratio on Return On Assets at PT. Nippon Indosari Corpindo Tbk. Associative type of research. The data analysis techniques used are the classical assumption test, multiple linear regression analysis, multiple coefficient test, coefficient of determination test, hypothesis test. using the help of SPSS Version 26. The population is PT financial report data. Nippon Indosari Corporindo. The sample used was purposive sampling by taking certain samples with data available for the last 10 years, namely from 2012-2021. Based on the results of research and analysis, it shows that Net Profit Margin, Debt To Equity Ratio, Total Asset Turn Over have a partially negative effect on Return On Assets at PT. Nippon Indosari Corporindo Tbk, while the Long Term Debt to Equity Ratio has a partial effect on PT's return on assets. Nippon Indosari Corpindo Tbk, Net Progit Margin, Long Term To Equity Ratio, Debt To Equity Ratio, Total Asset Turn Over have a significant effect on Return On Assets at PT. Nippon Indosari Corporindo Tbk